2021
DOI: 10.1101/2021.09.19.461013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome-transmitted miR-769-5p confers cisplatin resistance and tumorigenesis in gastric cancer by targeting CASP9 and promoting the ubiquitination degradation of p53

Abstract: Cisplatin resistance is the main cause of poor clinical prognosis in patients with gastric cancer (GC). Yet, the exact mechanism of cisplatin resistance remains unclear. Recent studies have suggested that exocrine miRNAs found in the tumor microenvironment participates in tumor metastasis and drug resistance. In this study, we discovered that cisplatin-resistant GC cells communicate with the tumor microenvironment by secreting microvesicles. The biologically active miR-769-5p can be integrated into exosomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Despite proof of miR-769 being involved in cell proliferation, invasion, and poor OS in HCC, 40 the clinical meaning of its presence in serum is still unclear. Evidence from other cancers 51,52 has shown that this miRNA is present in exosomes released by cancer cells. Therefore, focusing on the serum exosomal fraction alone could aid in interpreting the cancer-related information conveyed by miR-769.…”
Section: Discussionmentioning
confidence: 99%
“…Despite proof of miR-769 being involved in cell proliferation, invasion, and poor OS in HCC, 40 the clinical meaning of its presence in serum is still unclear. Evidence from other cancers 51,52 has shown that this miRNA is present in exosomes released by cancer cells. Therefore, focusing on the serum exosomal fraction alone could aid in interpreting the cancer-related information conveyed by miR-769.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell-based therapies were reported to inhibit GC apoptosis and follicular atresia [35] . In the current study, we focused on the effectiveness of relieving the CDDP-induced POI with hUCMSC-EVs instead of hUCMSCs in vitro and in vivo because hUCMSC-EVs are more stable and safer for clinical application.…”
Section: U N P R O O F E Dmentioning
confidence: 99%